Exploring the Relationship between the Clustering Degree of Children’s Business Formats and the Attractiveness of Commercial Centers in Wuhan by Modifying the Classic Retail Model - Zhuoran Shan; Xuehan Shen; Man Yuan (Land, 2022)
In recent years, the continued popularity of children’s consumption has made it a new factor that affects the attractiveness of Wuhan’s commercial centers. This study analyzes the characteristics of children’s business format agglomeration in Wuhan commercial centers based on the results of an on-the-spot investigation and estimates the passenger attraction of 66 commercial centers in the main urban area with the support of LBS data. In addition, we set up a control experiment group of commercial centers of various levels and explore the influence mechanism of the density of various types of children’s stores on the attraction of commercial centers by improving the classic retail model. The results indicate the following. (1) Children’s business formats in Wuhan’s commercial centers are active as a whole, and different types of children’s businesses have an unbalanced layout at the different levels of business centers. (2) There are both level ladder and internal level differences in the attractiveness of Wuhan commercial centers. (3) The direction and intensity of the influence of children’s business types on commercial centers of different levels differ. In city-level commercial centers, children’s education and entertainment formats play a role in promotion. In county-level commercial centers, the children’s education format is the most important, and overinvestment in the children’s department store format may not meet expectations. In community-level commercial centers, investment in children’s department stores yielded the best results. (4) Traffic impedance has a stable inhibitory effect at all levels of Wuhan commercial centers, which is in line with the classic retail gravity theory. Further, based on the above results, this paper puts forward suggestions on several types of adaptations that can be applied to children’s consumption stores at different levels of commercial centers to provide support for rationally utilizing the potential of the children’s consumption market.